Fatigue analysis of woven intraply carbon/kevlar reinforced epoxy hybrid composite at ambient and below ambient temperature - Hashim, Nurain (2019)
Investigations on fatigue behaviour of aircrafts’ composite structure at different temperature environment are important since it was reported that most aircraft’s structural failures were due to fatigue. In addition, cyclic loading of composite structures also experiences self-heating, which affects fatigue. Composite materials based on fabric constructions for aerospace structures are usually made up of woven fabric fibres with multitude of ply orientations and stacking sequences. Carbon/Kevlar reinforced epoxy composite is one example with improved impact resistance compared to homogeneous CFRP and still maintains its high tensile strength and fatigue strength. However, fundamental understanding on how hybrid composites affected by fatigue remains an active research topic. This work seeks to establish the tensile and low-cycle fatigue behaviour of woven intraply carbon/Kevlar reinforced epoxy hybrid composites at ambient and low temperatures. The effects of self-heating to the fatigue life and how different environmental temperature affect the self-heating were also investigated. A cooling chamber was designed to provide the cold environment for both tests. In this work, coupon shape of woven intraply carbon/Kevlar reinforced hybrid composites were fabricated and tested at three different directions at tensile and fatigue tests. Concurrently, thermocouples were attached at the samples’ surfaces for self-heating analysis. Differ from common unidirectional composite, best tensile strength was obtained at 0°, followed by 90° and 45° fibre direction as Kevlar fibre plays as the dominant role at 90° fibre direction. Tension-tension fatigue tests in ambient temperature were done at 0°, 45° and 90° fibre directions. Best fatigue strength found at 90° direction as it has the lowest life degradation rate, which is 4.1% of its UTS. However, only fatigue data at carbon direction is agreeing with the mean curves plotted using the MLE method. S-N curves have larger scatter for samples tested at 45° and 90°, where the life cycles can be seen to be divided into two different stages. At low temperature, hybrid composite samples were only tested in tensile test and fatigue test at 0° direction, at 0° C, -5°C and -10°C. This material showed higher tensile strength but more brittle properties at low temperature. The fatigue behaviour was improved as the life degradation rate at sub-zero temperature decreased from 5.2% to around 3% of its UTS. For self-heating observation, internal heat generation is significantly influenced by the fibre structures and its stiffening properties, not the stress level. At lower temperature, the heat generation also found to be influenced by the tensile modulus but did not affect the materials’ fatigue properties. All the results showed that the existence of different fibres in intraply hybrid composite gives large difference in tensile and fatigue properties. Low temperature condition also had affected the hybrid composites’ tensile and fatigue properties significantly.